Hubungan antara Pemimpin Abusif dan Organizational Citizenship Behavior : Apakah Agreeableness sebagai Pemoderasi? - Edi Cahyono (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2021)
The purpose of this paper is twofold. First, to examine the relationship between employee's perception of abusive leader and their organizational citizenship behavior. Second, to investigate the moderating role of agreeableness on this relationship. Data were collected from 200 employee's working at Rural Bank (BPR) in Surakarta, Indonesia through online questionnaires. The finding of the study confirms that abusive leader is negatively related to subordinates' organizational citizenship behavior. The study also reveals that agreeableness moderated the relationship between abusive leader and subordinates' organizational citizenship behavior